2016
DOI: 10.1016/j.matdes.2016.07.075
|View full text |Cite
|
Sign up to set email alerts
|

Micro-indentation based study on steel sheet degradation through forming and flattening: Toward a predictive model to assess cold recyclability

Abstract: Article history:In Cold Roll Forming (CRF) process sheet material undergo a complex set of deformation that entail complicated through thickness residual deformation. This paper, focuses on material behaviour in CRF processes, with regarding damage and material degradation. A roll forming process is taken as case study and experimental investigation using extensive microhardness mapping alongside FE simulation of the process are the basis of material damage study. Indentation on different cross-sectional cutti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A comparison was made to verify the developed model and experimental results presented by Falsafi and Demirci (2016) for the formability assessments after unbending the fold zones of a cold roll formed profile. Their experiment was carried out on the same material used in this study, and based on the reported change in formability and the geometrical parameters in their profile, three points are extracted for verification ( see Table 3 ).…”
Section: Verificationmentioning
confidence: 99%
“…A comparison was made to verify the developed model and experimental results presented by Falsafi and Demirci (2016) for the formability assessments after unbending the fold zones of a cold roll formed profile. Their experiment was carried out on the same material used in this study, and based on the reported change in formability and the geometrical parameters in their profile, three points are extracted for verification ( see Table 3 ).…”
Section: Verificationmentioning
confidence: 99%